Nursing typhus victims in the Second World War, 1942–1944: a discussion paper. (21st November 2013) - Brooks, Jane
Abstract Aims This article explores the care British nurses provided to victims of typhus during the Second World War. Background Typhus is associated with poverty and overcrowding. During wars in the pre‐antibiotic era, civilians were particularly susceptible to epidemics, which military governments feared would spread to their troops. Design This discussion paper draws on archival data from three typhus epidemics in the Second World War to examine the expert work of British nurses in caring for victims during these potential public health disasters. Data Sources The published sources for the paper include material from nursing and medical journals published between 1940–1947. Archival sources come from the National Archives in Kew, the Wellcome Library and the Army Medical Services Museum, between 1943–1945. Of particular interest is the correspondence with Dame Katharine Jones from nurses on active service overseas. Implications for Nursing Whilst epidemics of typhus are now rare, nurses in the present day may be required to care for the public in environments of extreme poverty and overcrowding, where life‐threatening infectious diseases are prevalent. This article has demonstrated that it is possible for expert and compassionate nursing to alleviate suffering and prevent death, even when medical technologies are unavailable. Conclusion Expert and compassionate care, adequate nutrition and hydration and attention to hygiene needs are crucial when there are limited pharmacological treatments and medical technologies available to treat infectious diseases. The appreciation of this could have implications for nurses working in current global conflicts.